Activation of the CpxRA System by Deletion of cpxA Impairs the Ability of Haemophilus ducreyi To Infect Humans - Spinola, Stanley M. (American Society for Microbiology (ASM), 2010)
Haemophilus ducreyi must adapt to the environment of the human host to establish and maintain infection in the skin. Bacteria generally utilize stress response systems, such as the CpxRA two-component system, to adapt to hostile environments. CpxRA is the only obvious two-component system contained in the H. ducreyi genome and negatively regulates the lspB-lspA2 operon, which encodes proteins that enable the organism to resist phagocytosis. We constructed an unmarked, in-frame H. ducreyi cpxA deletion mutant, 35000HPΔcpxA. In human inoculation experiments, 35000HPΔcpxA formed papules at a rate and size that were significantly less than its parent and was unable to form pustules compared to the parent. CpxA usually has kinase and phosphatase activities for CpxR, and the deletion of CpxA leads to the accumulation of activated CpxR due to the loss of phosphatase activity and the ability of CpxR to accept phosphate groups from other donors. Using a reporter construct, the lspB-lspA2 promoter was downregulated in 35000HPΔcpxA, confirming that CpxR was activated. Deletion of cpxA downregulated DsrA, the major determinant of serum resistance in the organism, causing the mutant to become serum susceptible. Complementation in trans restored parental phenotypes. 35000HPΔcpxA is the first H. ducreyi mutant that is impaired in its ability to form both papules and pustules in humans. Since a major function of CpxRA is to control the flow of protein traffic across the periplasm, uncontrolled activation of this system likely causes dysregulated expression of multiple virulence determinants and cripples the ability of the organism to adapt to the host.